Impact induced melting and the development of large igneous provinces - Jones, AP; Price, GD; Price, NJ; DeCarli, PS; Clegg, RA (ELSEVIER SCIENCE BV, 2002)
We use hydrodynamic modelling combined with known data on mantle melting behaviour to examine the potential for decompression melting of lithosphere beneath a large terrestrial impact crater. This mechanism may generate sufficient quantity of melt to auto-obliterate the crater. Melting would initiate almost instantaneously, but the effects of such massive mantle melting may trigger long-lived mantle up-welling that could potentially resemble a mantle hotspot. Decompression melting is well understood; it is the main method advocated by geophysicists for melting on Earth, whether caused by thinned lithosphere or hot rising mantle plumes. The energy released is largely derived from gravitational energy and is outside (but additive to) the conventional calculations of impact modelling, where energy is derived solely from the kinetic energy of the impacting projectile, be it comet or asteroid. The empirical correlation between total melt volume and crater size will no longer apply, but instead there will be a discontinuity above some threshold size, depending primarily on the thermal structure of the lithosphere. We estimate that the volume of melt produced by a 20 km diameter iron impactor travelling at 10 km/s may be comparable to the volume of melt characteristic of terrestrial large igneous provinces (similar to 10(6) km(3)); similar melting of the mantle beneath an oceanic impact was also modelled by Roddy et al. [Int. J. Impact Eng. 5 (1987) 525]. The mantle melts will have plume-like geochemical signatures, and rapid mixing of melts from sub-horizontal sub-crater reservoirs is likely. Direct coupling between impacts and volcanism is therefore a real possibility that should be considered with respect to global stratigraphic events in the geological record. We suggest that the end-Permian Siberian Traps should be reconsidered as the result of a major impact at similar to250 Ma. Auto-obliteration by volcanism of all craters larger than similar to200 km would explain their anomalous absence on Earth compared with other terrestrial planets in the solar system. (C) 2002 Elsevier Science B.V. All rights reserved.